Profiling occupational therapists’ preference for an international master’s program in occupational therapy: A needs analysis study - P. Sy, Michael; Pineda, Roi Charles; Concepcion D.C. Cabatan, Maria; E. Ching, Peñafrancia; Kaunnil, Anuchart; Saloko, Erayanti (Journal of Associated Medical Sciences, 2023)
Background: To advance occupational therapy knowledge and practice in Southeast Asia, it is pivotal that quality master’s degree programs in occupational therapy are in place. Such a program must respond to the needs of the region in terms of occupational therapy education, practice, and scholarship. By recognizing the diversity of the occupational therapy education and training in the region, it has become possible to consider alternatives in establishing a graduate program in occupational therapy through partnerships and consortia. In order to make an informed decision to decide whether co-creating a master’s program in occupational therapy through an international consortium within the region is possible or not, a needs assessment is warranted. Objectives: To describe the profile of occupational therapists living and working in the Southeast Asian region who would like to pursue a master’s degree in occupational therapy via an international consortium. Materials and methods: An online survey design was used to produce data that would be used to inform the co-creation of an international master’s program in occupational therapy. The survey questionnaire was designed specifically for this study and included three sections: 1) information and consent form; 2) demographic information; and 3) information about the need for and preferences on a master’s program in occupational therapy. Participants were recruited through professional organizations and various social media platforms of national and international occupational therapy groups. Results: Eighty-five final-year occupational therapy students and 143 occupational therapists from the Philippines, Indonesia, Thailand, and other countries completed the survey. Majority (62%) of the respondents was interested in pursuing a master’s degree in occupational therapy because they perceived that an advanced degree can enable specialization in practice, promote personal and professional development, and help generate new knowledge for the field. The characteristics of the envisaged international master’s program must be: 1) completed ideally in 1.5 to 2 years, 2) taken by part-time students who are also working practicing, 3) delivered via a hybrid arrangement (i.e., online and face-to-face) with a fixed weekly schedule, and 4) matriculated for USD 1,000 per semester. Conclusion: While this cross-sectional survey cannot encapsulate the totality of occupational therapists’ needs in terms of their professional development, the survey provided an empirical basis to inform decisions in the creation of a master’s program in occupational therapy jointly offered by an international consortium of Southeast Asian universities.